Promoting Students’ Scientific Habits of Mind and Chemical Literacy Using the Context of Socio-Scientific Issues on the Inquiry Learning - Wiyarsi, Antuni; Prodjosantoso, A. K.; Nugraheni, Anggiyani R. E. (Frontiers in Education, 2021)
This quasi-experimental study used a pre-/posttest design to investigate student's scientific habits of mind (SHOM) and chemical literacy. There were 32 eleventh-grade students for the experimental and control class. They were taken by random sampling. The experimental class applied inquiry learning via Predict-Observe-Explain-Extend (POEEd) using the socio-scientific issue (SSI) context, while the control class used a scientific approach that addressed the Indonesian national curriculum. Acid-Base Chemical Literacy Test (A-BCLT) consisted of 19 items that used four contexts. Argumentative question added on each context. The other instrument was the SHOM scale in the SSI context. The scale consisted of 20 items in seven factors of SHOM. A group of experts looked at both instruments to ensure content validity. Then, the empirical test showed that both instruments have good reliability. MANOVA as the inferential statistic technique was used to analyze the differences among the group. The results showed that there was a significant difference in SHOM and students' chemical literacy simultaneously. However, there was only a significant difference in students' chemical literacy on separate analyses. Students have a better scientific argument in the case of acid rain as SSI, but it was less good for consumption of ulcer medicine for fasting people. Meanwhile, for SHOM, students have better thinking in open-mindedness and objectivity factors but less on curiosity. Some of the interesting findings and their implications are discussed in this study. The integration of SSI in chemistry learning is important. It is meaningful in promoting students' thinking skills to become responsible citizens in the future